2018
DOI: 10.35386/ser.v18i1.43
|View full text |Cite
|
Sign up to set email alerts
|

Self Concept, Parental Socio-Economic Status and Academic Performance Among Senior Secondary School Students in Kebbi State, Nigeria

Abstract: The main thrust of the paper is to determine if there is any significant difference between socio – economic status, self-concept and academic performance of SS1 students in Kebbi State. The sample was made up of 360 (180 boys and 180 girls) drawn from the population of senior secondary school one (S.S.I) from six Senior Secondary Schools in Kebbi State. Akinboye’s Adolescent Personal Data Inventory (APDI) by Akinboye (1985) and the Adopted version of Parental Socio- Economic Status Questionnaire (PSESQ) by Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In a study related earlier, poor school or government administration, the poor commitment of teachers to their responsibilities, and family-related issues are among the factors that cause school/class absenteeism in Nigeria (Oghuvbu, 2008) like the findings of this study (as indicated in table 3). In a similar vein, as revealed by Aliero (2020), lack of parental care about education is one of the major factors that cause some students or children to leave school or classes, which was in the same vein with one reason stated in Table 3. Likewise, as indicated in this study (Table 3), the nature of teachers, when teachers are not doing their job of proper teaching, proper monitoring, and being studentcentred, there is a tendency for some students to abscond classes or schools entirely.…”
Section: Research Question Twomentioning
confidence: 65%
See 2 more Smart Citations
“…In a study related earlier, poor school or government administration, the poor commitment of teachers to their responsibilities, and family-related issues are among the factors that cause school/class absenteeism in Nigeria (Oghuvbu, 2008) like the findings of this study (as indicated in table 3). In a similar vein, as revealed by Aliero (2020), lack of parental care about education is one of the major factors that cause some students or children to leave school or classes, which was in the same vein with one reason stated in Table 3. Likewise, as indicated in this study (Table 3), the nature of teachers, when teachers are not doing their job of proper teaching, proper monitoring, and being studentcentred, there is a tendency for some students to abscond classes or schools entirely.…”
Section: Research Question Twomentioning
confidence: 65%
“…Education involves training a person or group of persons to read, write, and be proficient in specific aspects of life and to be able to conform to acceptable norms of society (Aliero, 2020;Odeniyi & Adeyanju, 2020). Nowadays, education is a pertinent pillar that is required for the growth and development of people, communities, individuals, and societies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Aliero et al (2022) posited that parent attitude is linked with improved behavior, regular attendance, and positive manners. In addition, showing a positive attitude toward your child's education includes constant involvement in their school activities and giving adequate care to their education and behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is very worrisome in Nigeria as the number of school dropout children is very large; instead of going to school, they wander the streets in a languishing situation (Aliero, 2020). Unfortunately, the issue of school dropout has been a problem of education in Sokoto state and is associated in one way or another with drug abuse (Bello et al, 2017;Abubakar et al, 2021;Abubakar et al, 2022).…”
mentioning
confidence: 99%